Cyber Fatigue in the Classroom: Unravelling the Complex Web of Technostress Among EFL Teachers - Muslimin, Afif Ikhwanul; Mukminatien, Nur; Ivone, Fransisca Maria (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2024)
The rapid technological change has affected education globally, ushering in both positive and negative consequences for teachers. This study focuses on the phenomenon of cyber fatigue among teachers, particularly in teaching English as a foreign language (EFL). Hence, it aims to comprehensively investigate the factors contributing to technostress, its effects on the teachers’ performance, and the strategies employed to cope with it, while also exploring the relationships among these variables. A mixed-method approach was employed, encompassing quantitative data collection through an online survey and qualitative insights gathered through interviews. The study involved 34 Indonesian EFL teachers spanning various educational levels. Findings revealed that the absence of a technology-based Teacher Professional Development (TPD) program, coupled with the rapid evolution of technology, heightened anxiety among EFL teachers and significantly impacted their teaching performance. However, the resilience and determination of these educators drove them to employ various coping mechanisms, which helped alleviate technostress to varying degrees. Interestingly, the study discovered that not all variables exhibited positive correlations. Specifically, coping strategies did not appear to be correlated with the factors triggering technostress or its effects, suggesting a complex and nuanced relationship in the realm of technostress management among teachers.